The Effect Of Using The Oxford Reading Club Application On Vocabulary Mastery Among Vocational School Students - Muhammad Arzeto Wijdan; Syafrizal Syafrizal; Yusti Fargianti (Lembaga Riset dan Inovasi Almatani, 2026)
This study aimed to investigate the effect of the Oxford Reading Club (ORC) application on students’ vocabulary proficiency through intensive reading combined with synonym–antonym strategies. This study employed a quantitative approach with a quasi-experimental design involving 60 vocational school students, divided into an experimental group and a control group. The experimental group was taught using the ORC application, while the control group received conventional instruction. Data were collected through pre-test and post-test and analyzed using descriptive statistics and an independent samples t-test after fulfilling normality and homogeneity assumptions. The findings revealed that both groups showed improvement; however, the statistical analysis indicated a significant difference between the two groups (Sig. = 0.04 < 0.05). This suggests that the use of the ORC application was more effective than conventional instruction in improving students’ vocabulary proficiency. The results highlight the potential of integrating digital reading platforms with structured vocabulary strategies to enhance learning outcomes in EFL contexts. Therefore, the ORC application can be considered as an alternative tool to support vocabulary learning, particularly in promoting engagement and contextualized language exposure among students. Keywords: Oxford Reading Club Application, vocabulary comprehension, EFL learners